Development and comprehensive investigation of a lightweight FBG accelerometer for small structure acceleration measurements - Muhammad Rais, Rahim; Hossain, MD Mofazzal; Mohd Firdaus, Hassan (IOP Publishing, 2024)
Despite their sensitivity potential, diaphragm-type fiber Bragg grating accelerometers with inertia mass are often too complex and large, limiting their suitability for measuring small structures. Designing a suitable accelerometer for small structures, where its weight must be less than one-tenth of the measured structure, is challenging. This paper introduces a compact, simplified, and fabricable non-inertia mass FBG accelerometer (FBGA-SD), featuring a longer FBG tunnel and a through-hole for monitoring. The proposed FBGA-SD is 16 × 16 × 10 mm, weighing 4 grams. Numerical and experimental results show good agreement, though amplitude sensitivity differs by 50%. The experimental sensitivity is 9.64 × 10−2 pm g−1, while transient response analysis gives 4.79 × 10−2 pm g−1, valid for 10–100 Hz excitation frequencies and up to 10.5 m s−2 base acceleration.